Snow White and the seven dwarfs. (connecticut : Grolier Enterprises, 1994)
A princess hides in the forest home of seven friendly dwarves when her stepmother's jealousy of her beauty grows deadly.
At head of title: Walt Disney's.
3.8
K-3.
K-3
Keywords: Fairy tales; Folklore -- Germany; Fairy tales; Folklore -- Germany